CYTOKINE MODULATION OF PROGENITOR CELL MIGRATION - Punia, Navneet (My University, 2011)
Rationale: Lung-homing of bone marrow (BM)-derived progenitor cells is associated with inflammatory and remodeling changes in asthma. Stromal cell derived factor-1α (SDF-1α) is a potent progenitor cell chemoattractant and its local production in the lung promotes lung homing of progenitor cells. The role of pro-inflammatory cytokines in promoting traffic of progenitor cells to the site of inflammation in asthma has not been investigated. The TH2 cytokines, interleukin (IL)-4 and IL-13, are key regulators of asthma pathology.
Objective: To investigate the role of IL-4 and IL-13 in modulating the trans-migrational responses of hemopoietic progenitor cells (HPC).
Methods: HPC were isolated from cord blood (CB) and peripheral blood (PB) and migrational and adhesive responses were assessed using transwell migration assays and adhesion to fibronectin-coated wells, respectively. Responding cells were enumerated by flow cytometry.
Results: IL-4 and IL-13 had no direct effect on progenitor cell migration. Pre-incubation with each of these cytokines primed SDF-1α stimulated migration of CB and PB-derived HPC (CD34+45+ cells) but not eosinophil-lineage committed progenitors (CD34+45+IL- 5Rα+ cells) or mature eosinophils to SDF-1α. For HPC, priming effects of IL-4 (0.1ng/ml) and IL-13 (0.1ng/ml) were detectable within 1hr and optimal at 18hr post- incubation and IL-4 was the more effective priming agent. Disruption of lipid rafts inhibited IL-4 priming of SDF-1α stimulated migration of HPC indicating that increased incorporation of CXCR4 into membrane lipid rafts mediates the cytokine primed migrational response of HPC. This was confirmed by confocal fluorescent microscopy.
Conclusions: IL-4 and IL-13 prime the migrational response of HPC to SDF-1α by enhancing the incorporation of CXCR4 into lipid rafts. The priming effect of these cytokines is specific to primitive HPC. These data suggest that increased local production of IL-4 and IL-13 within the lungs may promote increased SDF-1α mediated homing of BM-derived HPC to the airways in asthma.
Keywords: Progenitor cell migration; Priming; Interleukin-4; Interleukin-13; Stromal cell-derived factor-1α; Biological Phenomena, Cell Phenomena, and Immunity; Medical Immunology; Biological Phenomena, Cell Phenomena, and Immunity